Total syntheses of D-allo-1-deoxynojirimycin and L-talo-1-deoxynojirimycin via reductive cyclization - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (RSC Advances, 2014)
Synthesis of a polyhydroxypiperidine framework for L-talo-1-deoxynojirimycin and D-allo-1-deoxynojirimycin was achieved from L-tartaric acid by employing flash dihydroxylation and reductive lactamisation as the key steps.